Transcriptome Profiling Analysis of Phosphate-Solubilizing Mechanism of IPseudomonas/I Strain W134 - Wang, Shuaibing; Li, Yi; Zhang, Jie; Wang, Xiangying; Hong, Jianping; Qiu, Chen; Meng, Huisheng (Microorganisms (Basel), 2022)
Phosphate-solubilizing bacteria (PSB) can alleviate available phosphorus deficiency without causing environmental pollution, unlike chemical phosphate fertilizers. However, the phosphate solubilization mechanisms of PSB are still unclear. Transcriptome sequencing was used to analyze the expression patterns of differential expressed genes (DEGs) of the phosphate-solubilizing bacterium W134 under the conditions of soluble phosphorus (group A), insoluble phosphorus (group B), and lacking phosphorus (group C). Nine DEGs in three different groups were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Then, high performance liquid chromatography (HPLC) was applied to detect the concentrations and composition of organic acids. Compared with group A, Gene Ontology (GO) annotation showed that the cluster of W134 DEGs in groups B and C were basically the same. Besides, the results of enrichment Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway indicated that genes in the Citrate cycle (TCA cycle) pathway closely related to organic acid production were significantly upregulated. The qRT-PCR results were almost consistent with the expression trends of the transcriptome data. The HPLC results showed that the formic acid, ascorbic acid, acetic acid, citric acid, and succinic acid concentrations were significantly increased in group B and C (p < 0.05), while the contents of lactic acid and malic acid were significantly increased in group B (p < 0.05). The above results provided further validation that the upregulated genes should be related to W134 secretion of organic acids. Our study revealed several potential candidate genes and tried to explain phosphate solubilization mechanisms. This provides a new insight for calcareous reclaimed soil, and it will reduce the need of chemical phosphate fertilizers to promote environmentally friendly agriculture.